Pengembangan Desain Pesan Podcast Sebagai Media Pembelajaran Bahasa Inggris - Muhammad Ilwan Al-Asmahi; Novrianti Novrianti; Zuliarni Zuliarni; Fitri Maiziani (Jurnal Literasi Digital, 2022)
The development of Podcast Message Design is carried out as an effort to solve learning problems where the lack of learning media used by teachers during the learning process has an impact on the low interest in learning and motivation of students. Podcast is one of the media that can support student learning both at school and individually at home. Learning media can be used as an alternative to reduce problems in learning in students' listening skills, so that learning can be fun. This study aims to develop a Podcast media in the eighth grade English subject in order to produce a media that is valid and suitable for use by teachers and students. This type of research is research and development (Research & Development) with a 4D model (Defind, Design, Development, Disseminate). The product validity test developed was carried out by three validators consisting of one material expert and two media experts. The product trial or practicality was carried out to the students of class VIII SMP with a total of 22 students to test the practicality of the podcast media product for Class VIII SMP English Subjects that had been designed. Based on the results of the assessment of the material validator and media validator, the material validation results obtained an average of 4.8 categorized as "very suitable", the validation results from the media validator 1 obtained an average of 4.5 categorized as "appropriate" and the media validator 2 obtained an average of 4.78 is categorized as "very feasible". This podcast media is said to be "practical" based on a practicality test with an average value of 4.57. Based on the results of the validity and practicality tests, it can be concluded that the Media Podcast for Class VIII Junior High School English Subjects that was developed is suitable for use in English Class VIII Junior High School Subjects.